How mafias migrate: transplantation, functional diversification, and separation - Varese, Federico (Crime and justice, 2020)
Many policy makers and some academics believe that mafias move easily between countries and with little difficulty quickly become deeply rooted. The reality is more complicated. Mafiosi often move away from their home territories because they are forced to do so rather than because they relocate for strategic reasons; that kind of transplantation abroad tends to be unsuccessful. Whether transplantation succeeds depends on the presence of mafiosi and local factors, such as whether markets, construction, or illegal drugs are booming and poorly regulated. Under some conditions, transplantation results in wholesale separation between the original organization and the outpost. Mafiosi abroad often neither plan nor hope to achieve the kinds of control of territories, industries, and markets they exercise at home but to buy or sell illegal commodities, thereby engaging in a process of functional diversification.